Remediation of petroleum-contaminated Antarctic soil - Ferguson, Susan Harriet (2004)
Remediation of petroleum hydrocarbons in polar environments is more costly and logistically and technically more difficult than corresponding temperate and tropical contaminated sites. Bioremediation and in-situ chemical oxidation (ICO) are possible strategies which may overcome the financial and technical challenges associated with polar-region site remediation. ICO involves introducing reactive chemicals to contaminated soils so that organic contaminants such as petroleum hydrocarbons are oxidised to environmentally innocuous compounds, while bioremediation relies on microbial activity to achieve this. At Old Casey Station, East Antarctica (66¬¨‚àû17'S, 110¬¨‚àû32'E) more than 20 000 L of Special Antarctic Blend (SAB) diesel fuel was spilt over 15 years ago. Concentrations in the spill zone are still about 20 000 ppm and the rates of natural attenuation are relatively slow. The application of oxidative chemicals to the site did not significantly reduce petroleum hydrocarbon concentrations and would likely hinder biodegradation through the destruction of the subsurface microbial communities to below the level of detection for over 2 years. Bioremediation is considered the only likely viable alternative to natural attenuation or dig-and-haul procedures. The factors which were suspected of limiting microbial degradation of petroleum contaminants were temperature, nutrients and water availability. Their potential limitations were investigated with a series of radiometric treatability (microcosm) studies. A positive correlation between temperatures (between -2 and 42¬¨‚àûC) and the rate of 14C-octadecane mineralisation was found. The high rate of mineralisation at 37 and 42¬¨‚àûC was surprising, as most continental Antarctic microorganisms have an optimal temperature between 20 and 30¬¨‚àûC and a maximal growth temperature of less than 37¬¨‚àûC. 14C-octadecane mineralisation at nine different inorganic nitrogen concentrations (ranging from 85 to over 27 000 mg N kg-soil-H20 -1 ) was monitored. Total mineralisation ...